Stabilization system on an office-based ear surgical device by force and vision feedback. (April 2017) - Liang, Wenyu; Gao, Wenchao; Tan, Kok Kiong
Abstract: An "office-based surgical device" is a kind of device which aims to shift the conventional surgical procedures from the operating room to the confines of the doctor's/surgeon's office as well as to assist the surgeons to carry out the surgeries on the patients automatically or semi-automatically. In this paper, an office-based surgical device suitable for patients with Otitis Media with Effusion (OME) is introduced. Due to the office-based design, it is not possible to subject the patient to general anesthesia, i.e., the patient is awake during the surgical treatment with the device. To ensure a high success rate and safety, it is very important that the relative motion and the contact force between the tool set of the device and the tympanic membrane (TM) can be stabilized. To this end, a control scheme using force and vision feedback is proposed. The force feedback controller is a PID-based (proportional-integral-derivative) controller, which is designed for force tracking. The vision feedback controller is a vision-based motion compensator, which is designed to measure and compensate the head motion since it is equivalent to TM motion. Furthermore, the control scheme is implemented and tested in a mock-up system. The experimental results show that the proposed composite controller can achieve much better performance in force tracking than a pure force feedback controller. The performance can at least improve by 20% after augmenting the motion compensator, which helps the system to stabilize the relative motion indirectly and maintain the contact force precisely.